Gender relations and Reproductive Health in Zimbabwe: an assessment of cervical cancer among teenage mothers in Hurungwe Ward 13 - Marisa, Elina (2017)
Gender is one of the most important factors to consider in designing, managing and delivering reproductive health services. Yet gender may also be the least understood characteristic in terms of how women’s and men’s health needs differ and how those differences can be addressed. Adolescent mothers have been seen to be victims of gender disparities and as a result they have faced unprecedented health challenges such as STI infections and teenage pregnancies just to mention a few. This study sought to identify the extent to which gender relations have influenced the attainment of better reproductive health services for these adolescent mothers. The research was based on the case study of teenage mothers in Hurungwe district and how gender relations affected their attainment of a sample of fifty respondents who were identified through snowball sampling and purposive sampling, the research highlighted various issues of concern which included the existence ofa high rate of child marriages in the area under study, the role played by religion in infringing the rights of the girl child as well as the issue of the centralisation of facilities which offer cervical cancer screening services. After analysing the findings, various recommendations were laid down and these include the strong participation of stakeholders in information dissemination and ensuring that cervical cancer screening facilities are easily accessible to the populace